Remote measurement of high preeruptive water vapor emissions at Sabancaya volcano by passive differential optical absorption spectroscopy - Kern, Christoph; Platt, Ulrich (Journal of geophysical research. Solid earth, 2017)
Water (H2O) is by far the most abundant volcanic volatile species and plays a predominant role in driving volcanic eruptions. However, numerous difficulties associated with making accurate measurements of water vapor in volcanic plumes have limited their use as a diagnostic tool. Here we present the first detection of water vapor in a volcanic plume using passive visible-light differential optical absorption spectroscopy (DOAS). Ultraviolet and visible-light DOAS measurements were made on 21 May 2016 at Sabancaya Volcano, Peru. We find that Sabancaya's plume contained an exceptionally high relative water vapor abundance 6 months prior to its November 2016 eruption. Our measurements yielded average sulfur dioxide (SO2) emission rates of 800-900 t/d, H2O emission rates of around 250,000 t/d, and an H2O/SO2 molecular ratio of 1000 which is about an order of magnitude larger than typically found in high-temperature volcanic gases. We attribute the high water vapor emissions to a boiling-off of Sabancaya's hydrothermal system caused by intrusion of magma to shallow depths. This hypothesis is supported by a significant increase in the thermal output of the volcanic edifice detected in infrared satellite imagery leading up to and after our measurements. Though the measurement conditions encountered at Sabancaya were very favorable for our experiment, we show that visible-light DOAS systems could be used to measure water vapor emissions at numerous other high-elevation volcanoes. Such measurements would provide observatories with additional information particularly useful for forecasting eruptions at volcanoes harboring significant hydrothermal systems.